Smart mobility - Bernardo, Mafalda Ramos (2019)
Bernardo, M. R., de Castro Neto, M., & Aparicio, M. (2019). Smart mobility: A multimodal services study in the metropolitan area of Lisbon. In Atas da Conferencia da Associacao Portuguesa de Sistemas de Informacao 2019: 19ª Conferencia da Associacao Portuguesa de Sistemas de Informacao, CAPSI 2019 [19th Conference of the Portuguese Association for Information Systems, CAPSI 2019], Lisboa; Portugal; 11 October 2019 through 12 October 2019 (pp. 20). Associação Portuguesa de Sistemas de Informação.